Religious Moderation Volunteer Strategy in Improving Good Religious Practices of the Muslim Minority Community in Sari Laba Village, Sibiru-biru District - Abdullah, Radhinal; Rafida, Tien; Rohman, Fatkhur (Journal of Educational Sciences, 2025)
The Muslim minority community in Sari Laba Village, Sibiru-Biru District, faces limitations in understanding Islamic teachings correctly. Observations reveal that the community still practices Islam in a traditional manner. The presence of volunteers in the village plays an important role in promoting a more moderate understanding of Islam, particularly in the context of religious moderation. This study aims to identify: 1) The strategies implemented by volunteers in promoting religious moderation to sustain good religious practices; 2) The challenges faced by the Muslim minority community in practicing their religion; and 3) The best solutions offered by volunteers regarding religious moderation. This study employs a qualitative approach using theories that refer to indicators of religious moderation. The results show that: 1) Volunteers use persuasive and educational approaches with the community; 2) The main challenge lies in aligning local tribal traditions with Islamic teachings; and 3) The solutions offered by volunteers include organizing interfaith activities to foster mutual respect and tolerance.